A Cross-Sectional Survey Exploring Australian Pharmacists' and Students' Management of Common Oral Mucosal Diseases - Meng-Wong Taing; Joshua Choong; Vijayaprakash Suppiah; Sarira El-Den; Joon Soo Park; Michael McCullough; Leanne Teoh (MDPI AG, 2023)
Background: Oral mucosal conditions are commonly experienced in the general population and can have a negative impact on one's quality of life. This study evaluated the ability of Australian pharmacists and final-year pharmacy students to recognise and manage these common oral mucosal diseases through the use of case vignettes. Methods: Australian pharmacists and final-year pharmacy students were invited through social media, university learning management systems, or email to complete an online questionnaire consisting of six case vignettes covering topics relating to common oral mucosal presentations. Results: A total of 65 pharmacists and 78 students completed the questionnaire. More than 50% of the participants reported having seen all types of oral mucosal presentations, except for denture stomatitis, in their practice. The provision of best practice recommendations was reported by only 14%, 15%, 8%, and 6% of the participants for geographic tongue, hairy tongue, angular cheilitis, and denture-associated stomatitis, respectively, whereas 82% offered an appropriate anti-viral treatment for cold sore and 33% provided the best practice recommendations for oral thrush. Conclusion: This study emphasised the importance of further developing and integrating best practice oral healthcare training programs specifically tailored to the Australian pharmacy profession.